ANALISIS DAN DESAIN STRUKTUR BETON BERTINGKAT BANYAK BERDASARKAN PERBANDINGAN ANALISIS RESPONS SPEKTRUM DAN DINAMIK RIWAYAT WAKTU - Galuh Ayu Pratiwi; Widodo Widodo (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2017)
Indonesia is a country that has vulnerability to an earthquake. During the earthquake, the building has vertical and horizontal motion. Horizontal earthquake forces attack the weak points on structure that not strong enough and caused collapse building. To reduce the losses and casualities caused by the collapse of building especially multistory building, many seismic analyzes of structures are developed. This research explained the comparison of structural response between response spectrum and dynamic time history analysis to an irregular 9-story building. The building located in Yogyakarta with medium soil type and used as a hotel. The earthquake record that used for dynamic time history is El Centro 1979 earthquake (high frequency), El Centro 1940 earthquake (medium frequency), and Duzce earthquake (low frequency). Furthermore, the maximum result of structural response between them will be used for design purposes. The analysis in this research was done by ETABS version 9.6. The result showed that the maximum value of structural response such as displacement, story drift, momen force, shear force, and axial force caused by El Centro 1940 earthquake load. The next value caused by response spectrum load, Duzce earthquake load, and the smallest value caused by El Centro 1979 earthquake. The design calculation was done by using the result from dynamic time history analysis that caused by El Centro 1940 earthquake load because the load has the maximum response value.